First records of three Tripartiella species (Ciliophora, Oligohymenophora, Peritrichida) from freshwater fishes along Yangtze River in China - Tang, Fahui; Zhao, Yuanjun; Liu, Chunning (Zootaxa, 2013)
During parasitological surveys along Yangtze River in China, three species of trichodinid ectoparasites (Ciliophora, Oli-gohymenophora, Peritrichia) belonging to the genus Tripartiella Lom, 1959, were found from freshwater fishes. Tripar-tiella obtusa Ergens & Lom, 1970 and Tripartiella macrosoma Basson & Van As, 1987 were found from the same fish host, Rhinogobio typus; and Tripartiella orthodens Basson & Van As, 1987 was collected from another fish host, Pel-teobagrus nitidus. These three Tripartiella species all fall within the range of morphometry and agree closely in the overall appearance of the adhesive disc with the original populations. In the present work, both Tripartiella obtusa and Tripar-tiella orthodens are recorded for the first time in Asia. The host fish, Rhinogobio typus was recorded as a new host for Tripartiella obtusa and Tripartiella macrosoma. For each Tripartiella species, detailed descriptions are provided based the examinations of specimens prepared using the dry silver nitrate impregnation in the present study.